2011
DOI: 10.1007/s11746-011-1815-y
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile Including Trans Fatty Acid Content of Margarines Marketed in Mexico

Abstract: In this study, the fatty acid profile of 42 margarines marketed in Mexico was identified and quantified including the total trans fatty acids (TFA). The ratio of the sum of cholesterol-lowering fatty acids CLFA (cis-oleic, linoleic and a-linolenic fatty acids) to the sum of cholesterol-raising fatty acids CRFA (C12:0, C14:0, C16:0, TFA) and the x6/x3 ratio were calculated to evaluate the nutritional quality of the margarine samples. The results showed that the high content of C12:0, C14:0 and C16:0 fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…Trans‐18:1 isomers are considered to be quantitatively the major TFA in all dietary sources and, similarly to the results of previous studies (Aro and others 1998b; Bhanger and Anwar 2004; Hernández‐Martínez and others 2011), octadecenoic (C18:1) isomers were the main detected TFA in the current study. For dietary fats analyzed, with TFA content higher than 1 g per 100 g product, the contents of trans C18:1 varied from 2.4% to 31.6% (Table 1), whereas in all cases the quantity of trans PUFA were markedly lower, ranging from 0.14% to 5.83%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Trans‐18:1 isomers are considered to be quantitatively the major TFA in all dietary sources and, similarly to the results of previous studies (Aro and others 1998b; Bhanger and Anwar 2004; Hernández‐Martínez and others 2011), octadecenoic (C18:1) isomers were the main detected TFA in the current study. For dietary fats analyzed, with TFA content higher than 1 g per 100 g product, the contents of trans C18:1 varied from 2.4% to 31.6% (Table 1), whereas in all cases the quantity of trans PUFA were markedly lower, ranging from 0.14% to 5.83%.…”
Section: Resultssupporting
confidence: 90%
“…It is known that the FA composition of margarines and shortenings depends mainly on the selection of oil plants used in their manufacture e.g. coconut, sunflower or palm oil (Hernández‐Martínez and others 2011). In blended spreads the FA profile reflects, in addition, the FA content of the milk fat.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, not all authors make this mistake. When I compile a similar table as above by using the values of A. J. Dijkstra (&) Carbougnères, 47210 St Eutrope-de-Born, France e-mail: albert@dijkstra-tucker.be cis-18:2 listed in Table 3 in a paper by Hernández-Martínez et al [2]., anomalies like the above hardly occur: 37.30 ± 0.24 f, g S13…”
Section: Dear Editormentioning
confidence: 99%
“…The reason that I retabulated some experimental data from [1] and [2] is that the respective authors hardly indicated how they arrived at the significance (or lack of significance) of differences between the various samples. I therefore want to advocate that authors be more specific in explaining how they arrived at their conclusions and what standard errors they used.…”
Section: Dear Editormentioning
confidence: 99%
“…In HF65 and HF80A, SFA was responsible for why the AI was high, and this is besides palmitic acid, lauric acid, and myristic acid. Overall, the fatty acid composition of margarines is dependent on the lipid sources that are used, such as palm and coconut oil (Hernández-Martínez et al, 2011).…”
Section: Fatty Acids Compositionmentioning
confidence: 99%